End-of-Life Care for Transgender Older Adults - Lauren Catlett; Kimberly D. Acquaviva; Lisa Campbell; Dallas Ducar; Enoch H. Page; Jude Patton; Cathy Campbell (SAGE Publishing, 2023)
As the number of transgender older adults increases, the need for respectful and inclusive end-of-life (EOL) care for this population is becoming more apparent. Aging transgender adults often face discrimination, inadequate access to care, and poor quality of care. In response, we organized a think tank that invited participation from 19 transgender older adults, scholars in EOL care, and palliative care providers in the United States to generate recommendations for EOL care for transgender older adults. Subsequently, we conducted a qualitative descriptive exploration of the written record of think tank discussions for the purpose of identifying key EOL care considerations for transgender older adults. We identified four themes that highlight the importance of understanding the experiences of transgender older adults for the advancement of future research, policy, and education initiatives aiming to ensure inclusive and equitable provision of EOL care by nurses and other clinicians for this population.